Financing road projects by private finance initiative: current practice in the UK with a case study - Akbiyikli, Rifat; Dikmen, Seyyit U.; Eaton, David (Transport, 2011)
The necessity of funds for investment in capital intensive public projects has pushed public agencies to search for new procurement alternatives. Thus, in the early 1980s, the idea of private finance initiative (PFI) as a method of financing large-scale, capital intensive projects emerged in Australia. The method is aimed at resolving the shortage of public funds for major investments through the funding capability of private entities. Later, the method was widely used by other governments with the same name or different names such as BOT (build-operate-transfer) in the countries having different legal structures. This paper describes the mechanism of PFI used by the UK Government and evaluates three case studies in achieving the essential characteristics of adequate risk transfer and value for money to the taxpayer.First Published Online: 07 Jul 2011